2019
DOI: 10.1371/journal.pone.0214714
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of D-pigment dermocosmetic lightening product for solar lentigo lesions of the hand: A randomized controlled trial

Abstract: Solar lentigo, benign lesions which mostly appear on chronically, sun-exposed surfaces, are associated with ageing. Patients are increasingly requesting a more uniform skin texture, especially for hands. Treatment options include dermoabrasion, intense pulsed light, cryotherapy, peelings, and laser therapy. Topical compounds can be employed, in alternative or associated with dermatologic procedures. The current study was designed to evaluate solar lentigo hyperpigmentation, skin architecture and clinician and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…However, Arginelli et al demonstrated a quantitative restriction of natural DEJ destructuring on solar lentigines with the use of a dermocosmetic brightening product over a 12-month follow-up period. 37 Taken together, these findings suggest that the modulation in DEJ pattern seems to be not detectable in a short time frame, as in the present study. Future investigations with an extended treatment duration are needed to validate the long-term efficacy of our brightening product in correcting DEJ.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…However, Arginelli et al demonstrated a quantitative restriction of natural DEJ destructuring on solar lentigines with the use of a dermocosmetic brightening product over a 12-month follow-up period. 37 Taken together, these findings suggest that the modulation in DEJ pattern seems to be not detectable in a short time frame, as in the present study. Future investigations with an extended treatment duration are needed to validate the long-term efficacy of our brightening product in correcting DEJ.…”
Section: Discussionsupporting
confidence: 71%
“…Results showed that melanin density levels were reduced by 7% within the dark spots and 12% within their surrounding area after 2 months of full‐face application by Asian women. The observed skin‐brightening effect, validated by the SkinCam tool, became apparent within the first month of treatment and persisted throughout the study, suggesting a relatively rapid efficacy compared to other products in clinical trials 35–37 …”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations